Hubungan antara masa kerja dan postur kerja dengan keluhan muskuloskeletal pada petani daun bawang - Umboh, Aprillia Veronica; Kandou, Grace Debbie; Kalesaran, Angela Fitriani Clementine (Holistik Jurnal Kesehatan, 2026)
Background: Musculoskeletal disorders are a major global occupational health problem, characterized by pain and limited mobility, which can potentially lead to disability and reduced productivity. Working hours and work posture are among the occupational risk factors that cause musculoskeletal complaints. Long working hours cause cumulative exposure, while non-ergonomic work postures increase body load imbalance. Onion leaf farmers work in a bent posture, perform repetitive movements, and carry heavy loads, which put them at risk of musculoskeletal complaints. Purpose: To analyze the relationship between work duration and work posture with musculoskeletal complaints among onion leaf farmers. Method: A quantitative study using a cross-sectional approach was conducted in January 2026 in Makaaroyen Village, South Minahasa. The sampling technique employed non-probability sampling, with a sample size of 58 respondents. The independent variables in this study were length of service and work posture, while the dependent variable was musculoskeletal complaints. Data analysis was performed using univariate analysis in the form of frequency distributions and bivariate analysis using Spearman’s rank correlation. Results: The results showed that the majority of respondents had worked for more than 10 years (86.2%), had high-risk work postures (58.6%), and had high levels of musculoskeletal complaints (77.6%). Spearman's rank test showed a significant relationship between length of service and musculoskeletal complaints (p=0.002; r=0.402) with a moderate strength of relationship, and a highly significant relationship between work posture and musculoskeletal complaints (p<0.001; r=0.640) with a strong strength of relationship. Conclusion: There is a significant relationship between length of service and work posture with musculoskeletal complaints among spring onion farmers.   Keywords: Farmers; Musculoskeletal Disorders; Work Duration; Work Posture.   Pendahuluan: Gangguan muskuloskeletal merupakan masalah kesehatan kerja utama secara global, ditandai dengan nyeri dan keterbatasan mobilitas, yang berpotensi menyebabkan kecacatan dan penurunan produktivitas. Masa kerja dan postur kerja merupakan salah satu faktor risiko pekerjaan yang menyebabkan terjadinya keluhan muskuloskeletal. Masa kerja yang panjang menyebabkan paparan kumulatif, sedangkan postur kerja tidak ergonomis meningkatkan ketidakseimbangan beban tubuh. Petani daun bawang bekerja dengan postur membungkuk, gerakan repetitif, dan beban kerja berat yang berisiko menimbulkan keluhan muskuloskeletal. Tujuan: Untuk menganalisis hubungan masa kerja dan postur kerja dengan keluhan muskuloskeletal pada petani daun bawang. Metode: Penelitian kuantitatif dengan pendekatan cross sectional dilaksanakan bulan Januari 2026 di Desa Makaaroyen, Minahasa Selatan. Teknik pengambilan sampel menggunakan non-probability sampling dengan jumlah sampel yang digunakan sebanyak 58 responden. Variabel independen dalam penelitian ini adalah masa kerja dan postur kerja, sedangkan variabel dependen adalah yaitu keluhan muskuloskeletal. Analisis data yang digunakan univariate dalam bentuk distribusi frekuensi dan bivariate menggunakan Spearman Rank. Hasil: Mayoritas responden memiliki masa kerja >10 tahun (86.2%), postur kerja pada kategori risiko tinggi (58.6%), dan kategori keluhan muskuloskeletal yang tinggi (77.6%). Uji Spearman Rank menunjukkan, hubungan signifikan antara masa kerja dengan keluhan muskuloskeletal (p=0.002; r=.402) dengan kekuatan hubungan sedang, dan hubungan sangat signifikan antara postur kerja dengan keluhan muskuloskeletal (p<0.001; r=0.640) dengan kekuatan hubungan kuat. Simpulan: Terdapat hubungan signifikan antara masa kerja dan postur kerja dengan keluhan muskuloskeletal pada petani daun bawang.   Kata Kunci: Keluhan Muskuloskeletal; Masa Kerja; Petani; Postur Kerja.